Post-EVAR Thrombus Density on Late Non-Contrast CT Scans Predicts Successful Aneurysm Exclusion. (April 2021) - Rouer, Martin; Monnot, Antoine; Fuda, Michelangelo; Pochulu, Bruno; Palmier, Mickael; Thomas, Pascale; Benadiba, Laurent; Plissonnier, Didier
Purpose: The incidence of type II endoleaks (ELII) after endovascular aneurysm repair (EVAR) ranges from 10–44%. Aneurysm thrombus density after EVAR could predict successful aneurysm exclusion. Materials and Methods: Twenty-seven patients with an abdominal aortic aneurysm (AAA) who had a CT scan within the first 45 days (early group) post-surgery or after 7 months (late group) were included. Thrombus density was analyzed on non-contrast enhanced CT scans. Results: A total of 5/13 (38%) patients in the early group had an ELII and 9/14 (64.3%) in the late group had a persistent ELII since surgery. In the early group, thrombus density was similar in patients with or without an ELII (mean: 39.9 ± 4.8 vs. 41.9 ± 3.4, p = 0.7; median: 38.7 ± 4.8 vs. 39.7 ± 3.1, p = 0.8). In patients with an ELII, there was no difference in thrombus density at 45 days and after 7 months (mean: 39.9 ± 4.8 vs. 40.2 ± 2.1, p = 0.9; median: 38.7 ± 4.8 vs. 38 ± 2.6, p = 0.9). In patients without an ELII, thrombus density was significantly higher at 45 days than after 7 months (mean: 41.9 ± 3.44 vs. 25.7 ± 2.0, p = 0.005; median: 39.7 ± 3.11 vs. 24.4 ± 1.5, p = 0.004). In patients with an ELII, thrombus density was significantly higher after 7 months than in patients without an ELII (mean: 40.2 ± 2.1 vs. 25.7 ± 2.0. p = 0.001; median: 38 ± 2.6 vs. 24.4 ± 1.5, p = 0.003). Conclusion: Low thrombus density after EVAR on late unenhanced CT scans predicts aneurysm exclusion.